The Impact of Training on Employee Performance in a Selected Apparel Sector Organization in Sri Lanka (Global Journal of Management and Business Research, 2021)
The success of any organization depends considerably on the standard of its human capital. Training is a more powerful weapon among Human Resource Management practices, which helps to develop knowledge and skills of employees in an organization. The objective of the study was to investigate the impact of training on operational level employees' performance in a selected apparel organization in Sri Lanka. Through the analysis of 60 responses of randomly selected sample of machine operators; it shows that there is a strong, positive and significant relationship between training and performance with the correlation value of 0.817.The result of regression analysis indicates that there is a significant positive impact of training content and operational factors on employee performance. Upgrading the training content and identifying the training requirements specifically with a proper training duration are some of the recommendations that the researchers are suggesting improving employee performance.
Keywords: training content; operational factors; employee performance